MOTILITY AND VIABILITY OF FRIESIAN HOLSTEIN SPERMATOZOA IN THREE DIFFERENT EXTENDER STORED AT 5oC - Arifiantini, R.I.; Purwantara, B. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The aims of this study was to compare Tris egg yolk and Citrate egg yolk extender andsupplementation of fructose on citrate egg yolk on the quality of Friesian Holstein (FH) bull semenstored at 5 oC. Semen was collected from 5 FH bulls using an artificial vagina. The semen wereevaluated macroscopic and microscopically. The semen divided into three tubes and extended with Trisegg yolk (TEY), Citrate egg yolk (CEY) or Citrate fructose egg yolk (CFEY). Extended semen wasstored at 5 oC and evaluate daily for sperm motility and viability. There was no significant differences(P>0.05) on the sperm viability among three extender, for every time observation during 144 hours ofstorage. This similar finding found on the sperm motility in all extender for 48 hours of storage. Thesperm motility in TEY demonstrated significantly greater (P<0.05) than in CFEY and CEY extender at72 to 120 hours storage. In the end of storage, sperm motility in TEY (35.2 ± 4.1%) and CFEY (33.5 ±2.71%) extender statistically indicated no significant different, and both were greater than CEY. Inconclusion, CFEY support the sperm motility as good as TEY of FH bull.